Language contact in medieval Frisia: Middle Low German spelling interferences in Old East Frisian manuscripts - Rolf H. Bremmer Jr. (Filologia Germanica, 2024)
In the course of the Middle Ages, speakers of Frisian increasingly came under pressure of Low German. Eventually, in the fifteenth century, Low German gained the upper hand, first in writing, but soon enough in speaking too, leading to a complete language shift in the Frisian lands east of the river Lauwers. Previous scholarship on this topic focused on Low German loans in Old East Frisian. However, a detailed studies reveals that also the spelling habits of Frisian scribes reveal an increased Low German interference.